(untitled) (diségno, 2022)
The enhancement of the archival architectural heritage, in terms of preservation, has favored the documentation and investigation of projects and buildings. The significance of constructing 3D digital models in the domain of architecture is already a well-established idea. In addition, the digital reconstruction of hand-made drawings contributes to the deepening of the study of unbuilt. In this sense, the representation only by orthogonal projections is insufficient to perceive the spaces, on the other hand, animation allows us to include time by simulating the displacement of a virtual spectator. In the unbuilt project for the Museum of Contemporary Art at the University of São Paulo, MAC USP (1975), designed by architect Paulo Mendes da Rocha, the circulation system is organized by a set of ramps, footbridges, and stairs, which promotes the contemplation of the internal spaces. Using digital simulation, this article analyzes the temporal sequence of approach to this building, its accesses, penetration into interior spaces, and the multiple views from six paths resulted by animations. Rendering, animation, and axonometric resulting from 3D digital model, allowed us to analyze the circulation system, particularly the emphasis of the ramps in this project from the concept of promenade architecturale. The original contribution of this article is highlighting the singular circulation system adopted by the architect in this unbuilt project by digital simulations.